2019
DOI: 10.3389/fimmu.2019.02864
|View full text |Cite
|
Sign up to set email alerts
|

Activatory Receptor NKp30 Predicts NK Cell Activation During Controlled Human Malaria Infection

Abstract: Natural killer (NK) cells are known to be activated during malaria infection, exhibiting both cytokine production and cytotoxic functions. However, NK cells are heterogeneous in their expression of surface activatory and inhibitory receptors which may influence their response to malaria parasites. Here, we studied the surface marker profile and activation dynamics of NK cells during a Controlled Human Malaria Infection in 12 healthy volunteers. Although there was significant inter-patient variability in timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…59 Experimental, controlled human malaria infections (CHMI) have given valuable insights into the activation of NK cells during primary infection in malaria-na€ ıve individuals. Surprisingly, despite the known role for inflammatory cytokines (IL-12, IL-18) in activating less differentiated NK cells, the primary acute response during CHMI is characterised by activation (CD69 expression) of NKp30 + NK cells distributed across the differentiation spectrum but with CD56 dim cells dominating over CD56 bright cells 60 ; interestingly, these expansions were closely linked to the course of parasitaemia and resolved after treatment. 60 It is likely that both expansion and homing of activated CD56 bright NK cells toand their retention insecondary lymphoid tissues contribute to redistribution of NK cell subsets during active malaria infection.…”
Section: Impacts Of Chronic Persistent or Recurrent Infection On Nk mentioning
confidence: 99%
“…59 Experimental, controlled human malaria infections (CHMI) have given valuable insights into the activation of NK cells during primary infection in malaria-na€ ıve individuals. Surprisingly, despite the known role for inflammatory cytokines (IL-12, IL-18) in activating less differentiated NK cells, the primary acute response during CHMI is characterised by activation (CD69 expression) of NKp30 + NK cells distributed across the differentiation spectrum but with CD56 dim cells dominating over CD56 bright cells 60 ; interestingly, these expansions were closely linked to the course of parasitaemia and resolved after treatment. 60 It is likely that both expansion and homing of activated CD56 bright NK cells toand their retention insecondary lymphoid tissues contribute to redistribution of NK cell subsets during active malaria infection.…”
Section: Impacts Of Chronic Persistent or Recurrent Infection On Nk mentioning
confidence: 99%
“…Our results support the prior observation that during MCMV infection high cell surface density of the Ly49H receptor on mouse NK cells facilitates the NK cell memory response ( Grassmann et al, 2019 ). Other studies have reported that NKp30, NKp46, or/and NKG2D mediate human NK cell–myeloid cell crosstalk and NK cell–tumor interactions to facilitate innate lymphoid cell expansion ( Matta et al, 2013 ; Trabanelli et al, 2017 ; Hart et al, 2019 ; Walk and Sauerwein, 2019 ). This suggests that the in vivo persistence observed in acute myeloid leukemia patients undergoing cytokine-induced memory-like NK cell therapy might be partly due to higher activating NK receptor levels, as was reported for NKp30, NKp44, NKp46, and NKG2D ( Romee et al, 2016 ; Foltz et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…NKp30 is an activating receptor that plays a central role in the resistance to infectious disease [33]. Its high baseline expression favours a rapid reaction of NK cells to infections such as malaria [34]. The expression of NKp30 is likely hormone-dependent as its expression has been observed to change during the different phases of the menstrual cycle [35].…”
Section: Discussionmentioning
confidence: 99%